If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -2x = 12 + -1(6x + 3) Reorder the terms: 17 + -2x = 12 + -1(3 + 6x) 17 + -2x = 12 + (3 * -1 + 6x * -1) 17 + -2x = 12 + (-3 + -6x) Combine like terms: 12 + -3 = 9 17 + -2x = 9 + -6x Solving 17 + -2x = 9 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 17 + -2x + 6x = 9 + -6x + 6x Combine like terms: -2x + 6x = 4x 17 + 4x = 9 + -6x + 6x Combine like terms: -6x + 6x = 0 17 + 4x = 9 + 0 17 + 4x = 9 Add '-17' to each side of the equation. 17 + -17 + 4x = 9 + -17 Combine like terms: 17 + -17 = 0 0 + 4x = 9 + -17 4x = 9 + -17 Combine like terms: 9 + -17 = -8 4x = -8 Divide each side by '4'. x = -2 Simplifying x = -2
| -16+5x=-7(-6+8n)+3 | | 5x-3(2x+3)=3(x+11) | | y-10=-16 | | 7-2x=11+7x | | 7+5b=-24 | | (X+10)+70+x=180 | | -48=k(-9) | | -2n+(7n)+5=59 | | 2(2w)+2(2w)=102 | | 18y-9y=63 | | 126=0 | | 5(x+5)=3(3-x)-13 | | 5x^2=7x+4 | | 2-5(2x-1)=5 | | 5x+2x-3=-3x+3+10x | | 4x^2+130-504=0 | | 4x+x-61=34 | | -22x-6x=-28 | | 8-5(2-x)=14 | | 26.92=5g+3.57 | | -24s+-53=39+-15 | | -2+5a+6a=8a-8 | | (3+y)+2y+y=27 | | 8.22=3x+2.55 | | 12x+2=1x-53 | | -4x+2(5x)-6=-3x-39 | | -4p-4=11-5p+4p | | 2x/3=8-3x | | 3e=457 | | 1.5x-1.2=3.1x | | 3x-202+8x=73 | | x+5x-4x=12x-28 |